DISORDERS OF INTESTINAL MICROBIOCENOSE AND ENTEROSORPTION - A.I. Khavkin ("Paediatrician" Publishers LLC, 2009)
This lecture presents modern approach to treatment of disorders of intestinal microflora and, as a result, the reasons of indigestion. A contribution of dysbiosis to alteration of intestinal transition, disorders of nutritive tolerance and development of allergy was marked. Special attention was given to analysis of active enterosorption - a pathogenetic method of correction of endotoxinemia, which can be reflection of microbe misbalance.Key words: intestinal microflora, dysbiosis, enterosorption.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(2):94-98)